Cutaneous neurogenic inflammation in the sensitized acupoints induced by gastric mucosal injury in rats. - Wei He; Xiao-Yu Wang; Hong Shi; Wan-Zhu Bai; Bin Cheng; Yang-Shuai Su; Xiao-Chun Yu; Xiang-Hong Jing; Bing Zhu (BMC Complementary & Alternative Medicine, 2017)
Background: In acupuncture practice, the most important step is to confirm the location of a sensitized acupoint which reflects a diagnosis and can be stimulated with a specialized needle to treat the disease. Abnormal symptoms such as hyperalgesia or allodynia at the sensitized acupoints in patients with visceral disorders are considered to be in relation with referred pain and neurogenic inflammation. Yet, limited study has investigated the cutaneous neurochemical changes of the sensitized acupoints. Methods: The resent study developed an animal model of gastric mucosal injury (GMI) by HCl administered into the stomach of the rats. Evans Blue (EB) dye was applied by injection of tail vein after mucosal damage to observe the neurogenic plasma extravasation dots in the skin of the rats. The EB dots extravagated in the skin were compared with locations of acupoints. Immnohistochemistry analysis was used to detect the expression of calcitonin gene-related peptide (CGRP)- or substance P (SP)-labeled nerve fibers, histamine (HA)-, serotonin (5-HT)-, and tryptase-labeled cells in EB dots. Images were recorded and analyzed by Confocal imaging system and Olympus Image Processing Software. Results: The results showed that GMI resulted in neurogenic plasma extravasation in the skin of the acupoints over the back and abdomen, which mostly occurred in the T9-11 dermatomere. The EB extravasation dots appeared after GMI and disappeared gradually during the natural self-recovery of the gastric mucosa. More SP and CGRP positive nerve fibers were distributed in EB dots than that in regions beside EB dots and in the control, mostly distributed in the nerve fibers around both the vessels and root of hair follicle. Mast cells also aggregated and degranulated to release algogenic substances of 5-HT and HA around the vessels in areas of the EB dots. Conclusions: Our results indicates that the mechanism of EB extravasation in the skin of the acupoints induced by GMI are closely related to neurogenic inflammation, and that the high expression of local allergic substances and nociceptive neuropeptides in the local skin including SP, CGRP, HA, 5-HT, and mast cell tryptase may be the underlying mechanism of the acupoint sensitization.